2012
DOI: 10.1159/000345919
|View full text |Cite
|
Sign up to set email alerts
|

Management of Obesity-Induced Kidney Disease: A Critical Review of the Literature

Abstract: It is well established that obesity is a risk factor for the development of chronic kidney disease (CKD) and may promote the progression to end stage renal disease (ESRD). Therefore, it is strongly suggested that reduction of body weight can be an important intervention in order to reduce the prevalence of renal impairment. The current article describes extensively the already published trials which have studied the association between weight loss and kidney disease. The weight management programs include surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 109 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…Thus, the fenofibrate-induced elevation of serum adiponectin levels may contribute to the concomitant decrease in UAE, because of the renoprotective effects of adiponectin. Consistently, unpublished data from a previous trial performed by our study group showed that the percentage change in circulating HMW adiponectin over 3 months of fenofibrate treatment was negatively correlated with the percentage change in urinary albumin to creatinine ratio (ACR) (rZK0.648, PZ0.043) (Christou et al 2012).…”
Section: The Role Of Adiponectin In Medical Interventions Influencingsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, the fenofibrate-induced elevation of serum adiponectin levels may contribute to the concomitant decrease in UAE, because of the renoprotective effects of adiponectin. Consistently, unpublished data from a previous trial performed by our study group showed that the percentage change in circulating HMW adiponectin over 3 months of fenofibrate treatment was negatively correlated with the percentage change in urinary albumin to creatinine ratio (ACR) (rZK0.648, PZ0.043) (Christou et al 2012).…”
Section: The Role Of Adiponectin In Medical Interventions Influencingsupporting
confidence: 88%
“…Obesity per se can induce renal injury resulting in albuminuria, independently of the presence of diabetes and hypertension which are often associated with obesity (Kiortsis & Christou 2012). Specifically, the renal effects of obesity can be divided into structural and functional effects.…”
Section: The Role Of Adiponectin In Obesity-induced Albuminuriamentioning
confidence: 99%
See 1 more Smart Citation
“…73 However, only a few studies have studied the effects of a healthy lifestyle on kidney function. 74 Small studies suggested improvements in estimated GFR and/or albuminuria with low-calorie diets, especially when weight loss has been significant. Although even small amounts of regular physical activity (150 min/wk) reduce all-cause and particularly, cardiovascular mortality, 75 the effects of physical activity on kidney function have not been studied in obese CKD patients.…”
Section: Treatment Of Obesity In Ckdmentioning
confidence: 99%
“…Another study reports a significant improvement in renal parameters after bariatric surgery. 74 Alexander et al 82 reported that, in a series of 45 CKD patients who had undergone gastric bypass, nine patients had resolution, improvement, or stabilization of their kidney function. A study of 233 severely obese patients before and 12 months after bariatric surgery showed that mean estimated GFR increased in obese CKD patients.…”
Section: Treatment Of Obesity In Ckdmentioning
confidence: 99%